AWAKENING TEACHER LEADERS: A NEW PARADIGM IN EDUCATION FOR SCHOOL AND STUDENT SUCCESS - Soares, Lina (PUPIL: International Journal of Teaching, Education and Learning, 2020)
For decades, teachers have fulfilled many leadership roles from serving on committees to functioning as department chairs and grade-level leaders in selecting instructional materials and designing curricula. Advocacy for expanded leadership opportunities has become increasingly important in the United States. In response, state policy-makers have established advanced degrees to promote teacher leadership. Research has further shown that when teachers function in leadership roles, the results are positive for school reform, student achievement, and the profession. Because teachers are on the frontline and interact daily with students, teacher leadership is grounded by a set of principles that acknowledges teachers are positioned to make informed decisions and promote needed changes concerning the improvement of the teaching and learning process. While teacher leadership is often viewed as a set of knowledge and skills that enhance the teaching profession, the writer believes teacher leadership is an optimal strategy for school and student success. Teacher leadership is a win-win strategy for public education in states that have endorsed the teacher leadership principle. This contribution aims to bring awareness to teacher leadership. Based on a university advanced degree course the writer has developed, the paper provides a research-based framework for promoting teachers as leaders and ultimately leading to school improvement and student success.